Evaluation of CropSyst Model for Simulating Green Area Index, Soil Water and Yield of Psyllium in Hyper Arid Partially Irrigated Zone of Rajasthan - Soni, M L; Yadava, N D; Jat, Sita Ram; Gulati, I J; Rathore, V S; Birbal, Birbal; Kumawat, Amit; Glazirina, M (Annals of Arid Zone, 2017)
Cropping systems model (CropSyst) was calibrated using the experimental data of crop parameters, soil profile data and observed daily weather data of experimental site for 2012-13 and validated the experimental data of crop growth, yield parameters and soil moisture for 2013-14 for psyllium crop grown at farmer’s field in IGNP stage-II of Bikaner. The results of the present study showed that the CropSyst model calibrated seed yield, above ground biomass and soil moisture reasonably well. The simulated seed yield of psyllium (429 kg ha-1) matched well with the observed yield (462 kg ha-1) with relative error of 7.1%. The observed above ground biomass (AGB) at harvest (1085 kg ha-1) also matched with simulated AGB (997 kg ha-1) with relative error of 8.1%. During validation of the model during 2013-14, prediction of simulated seed yield (597 kg ha-1) was very good and matched well with the observed seed yield (557 kg ha-1) with relative errors of 7.3%. However, the simulated AGB (1894 kg ha-1) of psyllium was over predicted as compared to observed AGB (1395 kg ha-1) with relative errors of 35.8%. The simulated green area index (GAI) was not properly captured by the model. The simulated N-uptake (34.0 kg ha-1) was moderately higher than observed N-uptake (26.0 kg ha-1). Simulated soil moisture was well predicted and excellent matched with observed values in most of the layers. About half of total water applied lost by deep drainage with water productivity of 0.17 kg m-1.